116 AKAP-ASSOCIATED SPERM PROTEIN OVEREXPRESSION IN OVARIAN CANCER. Issue 1 (1st January 2007) - Ferrari, R.; Grizzi, F.; Fiore, B.; Yuefei, Y.; Frezza, E. E.; Jenkins, M. R.; Cobos, E.; Chiriva-Internati, M.
Abstract : Purpose: Annually in the United States, ovarian carcinomas are diagnosed in approximately 22, 000 women, causing 16, 000 deaths. Most malignant ovarian tumors are epithelial ovarian cystadenocarcinomas. Women from northern and western Europe and North America are affected most frequently, whereas women from Asia, Africa, and Latin America are affected least frequently. AKAP-associated sperm protein (ASP), also known as ropporin-1 like (ROPN1L), is a protein that interacts with the amphipathic helix region of A-kinase anchoring protein 3, 110 (AKAP3, 110); the AKAPs protein family binds to signal transduction molecules and is responsible for signaling and trafficking within the cell. Even if ASP has yet not been deeply investigated, its role in sperm motility and cytoskeletal reorganization during spermiogenesis has been suggested. Since the expression of ASP has been shown to be restricted to the testis, we decided to further investigate its presence in ovarian malignancies. Methods: Our study evaluated ASP presence at the protein level in paraffin-embedded human ovarian cystadenocarcinomas by immunohistochemistry. Thirty-three different cases of cystiadenocarcinoma were considered: after deparaffining; the slides underwent antigen retrieval in a thermostatic bath (Fisher Scientific) at 98°C for 30 minutes. After 15 minutes blocking in H2 O2 3%, the primary antibody anti-ASP (Imgenex, San Diego, CA) was added for 1 hour, followed by 30 minutes' exposure to the envision secondary antibody system (Dako, Carpinteria, CA). The reaction result was highlighted through the DAB staining system (Dako). Summary: Eight of the 33 evaluated samples (24.2%) gave evidence of ASP expression. Between the eight positive samples, in six cases (75%), a strong staining was shown, whereas a weak level of expression was detected in the remaining two (25%). Conclusion: In the investigated human cystadenocarcinomas, ASP was expressed at the rate of 24.2%. In most (75%) of our positive findings, ASP showed a strong staining, giving evidence that it was actually overexpressed. To our knowledge, this is the first report of an ASP investigation in cases of ovarian cystadencarcinomas. Further studies are needed to consider ASP as a novel cancer testis antigen (CTA) in ovarian malignancies.